2017
DOI: 10.4067/s0034-98872017000901106
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de sueño y rendimiento académico en alumnos de educación secundaria

Abstract: A bad sleep quality influences academic performance in these students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…To overcome this problem, further studies with more universities and locations can also allow testing other hypothesis related to the association of burnout with teaching styles and perceived or actual student support. Other meaningful associations can be applied to further studies, for instance, between burnout and subjective well-being (Oyanedel et al, 2015) or between burnout and sleep quality (Bugueño et al, 2017).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…To overcome this problem, further studies with more universities and locations can also allow testing other hypothesis related to the association of burnout with teaching styles and perceived or actual student support. Other meaningful associations can be applied to further studies, for instance, between burnout and subjective well-being (Oyanedel et al, 2015) or between burnout and sleep quality (Bugueño et al, 2017).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…These results are supported by a previous study involving students that showed a relationship between sleep quality and anxiety, as well as a high prevalence of anxiety in physically inactive students [ 30 ]. Poor sleep quality was also associated with low academic performance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To subjectively assess sleep quality, an excellent recognized tool is the "Pittsburgh Sleep Quality Index (PSQI)" of 1989 [9]. The questionnaire evaluates seven sleep components: subjective quality of sleep, sleep latency, sleep duration, sleep efficiency, sleep disorders, medication use, and daytime dysfunction.…”
Section: Data Collection and Analysismentioning
confidence: 99%